Uterine fibroids, laparoscopic surgery and morcellation: comparative analysis of the results of organ-preserving operations - Alexander A. Seregin; Anastasiia B. Nadezhdenskaia; Anna S. Makarova; Polina L. Sheshko; Anna V. Tregubova; Eleonora V. Kirilova; Daria K. Kopnenkova; Stanislav M. Pronin; Grigory N. Khabas; Alexandra V. Asaturova; Dmitry L. Ovodenko (IP Berlin A.V., 2021)
Aim. To conduct a comparative analysis of the results of organ-preserving laparoscopic operations performed for uterine fibroids with the use of plastic containers for morcellation and without it. Materials and methods. We examined 57 patients with a diagnosis of uterine fibroids who were admitted to the Department of Innovative Oncology and Gynecology of the Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology for organ-preserving surgical treatment. To achieve the goal of the study, the patients were divided into the following groups: the main group 29 patients who underwent laparoscopic myomectomy and morcellation of removed nodes using plastic containers. The control group consisted of 28 patients who underwent morcellation during laparoscopic myomectomy without the use of plastic containers. Results. The duration of laparoscopic operations performed using plastic containers main group was 85.6925.87 minutes. Laparoscopic conservative myomectomies, performed without the use of limiting systems, took a slightly longer amount of time control group 88.7530.36 minutes. There were no statistically significant differences, but in the second group, more prolonged sanitation of the abdominal cavity and removal of small fragments of myomatous nodes after morcellation outside the sacs were required. Autoinfusion was used in 6 (20.69%) patients in the main group, in 7 (25%) patients in the control group. Blood transfusion was not used in any case. Average blood loss was 120.6967.50 ml in the main group, 125.0099.54 ml in the control. The duration of hospitalization in the main group was 4.661.76 days, in the control group 5.793.62 days. In the main group, histological examination revealed leiomyoma in all cases, leiomyoma was detected in 96.4% (27 patients) of cases in the control group, and leiomyosarcoma in 1 patient (3.6%). Conclusion. In all groups of patients, there was a favorable course of the postoperative period, early activation of patients. In the group of laparoscopic operations, one patient (3.6%) after morcellation of the myomatous node without the use of a plastic container was found to have leiomyosarcoma. The use of plastic containers in our study did not increase the duration of operations and did not affect the volume of blood loss, the frequency of intra- and postoperative complications. In contrast, the operation time was slightly higher among patients who were operated without the use of containers. In all likelihood, this was due to the fact that the morcellation stage itself took longer, since it was required to extract small fragments of myomatous nodes, as well as thorough and prolonged sanitation of the abdominal cavity. It should be noted that the use of plastic containers, of course, requires the development of certain skills from the surgeon, taking less and less time in parallel with the learning curve. Of course, further studies are required to assess the risk of tumor spread in patients undergoing surgery using plastic containers, but preliminary data indicate that ablastic morcellation can and should be used in organ-preserving surgery for uterine myoma.